Modeling of Dynamical System Piloted by Discrete Subsystem Based on Bond Graph Approach - Ben Salem J; Lakhoua M.N.; El Amraoui L (Institute of Advanced Engineering and Science, 2017)
This paper is a contribution to the analysis and modeling of a mechatronic system with dynamic behavior that is controlled by a digital computer. In this paper, a bibliographic research on mechatronic systems is presented by specifying a case study of the Anti-lock Braking System (ABS). Then, a methodology of systemic modeling of the ABS system based on two methods Structured Analysis Design Technique (SADT) and bond graph (BG) is proposed. The model created is validated with three software programs: CarSim, 20 Sim and Simulink.